"Apparatus of Belief": Prayer, Material Objects/Media and Spiritual Warfare in African Pentecostalism. (2nd December 2020) - Benyah, Francis
Abstract: The neo-Pentecostal churches which burgeoned between the late 1970s and early 1990s, have grown not only in numbers but have also become the representative face of global Christianity. One significant feature of the neo-Pentecostal movement is their emphasis on prayer and the need for one to be "born again" and enjoy life devoid of the manacles of the devil. To achieve this, there is the need for one, through the power of the Holy Spirit, to discern the activities of evil or demonic forces and through prayer and the blood of Jesus, neutralise their diabolic plans. This is usually referred to as "spiritual warfare". Focusing on the theory of mass mediation and religious sensation, this article reveals how material objects and/or media such as stickers, wristbands and handkerchiefs expressed in this article as "apparatus of belief", acquire enchanted qualities and are, therefore, used as weapons of protection to fight against the enemy to destroy destructive powers in people's lives.